2019
DOI: 10.1002/ps.5615
|View full text |Cite
|
Sign up to set email alerts
|

Altering of host larval (Spodoptera exigua) calcineurin activity in response to ascovirus infection

Abstract: BACKGROUND Calcineurin (CaN) is involved in numerous cellular processes and Ca2+‐dependent signal transduction pathways. According to our previous transcriptome studies, thousands of host larval (Spodoptera exigua) transcripts were downregulated after the infection of Heliothis virescent ascovirus 3h (HvAV‐3h), while the Spodoptera exigua calcineurin genes (SeCaNs) were significantly upregulated. To understand the regulation of SeCaNs in S. exigua larvae during the infection of HvAV‐3h, the functions of CaN su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…At present, the most commonly used research method for gene detection is qRT-PCR, which detects the expression level of the target gene quickly and with great sensitivity (Dong et al 2022; Liu et al 2022a; Yang et al 2021). The most commonly used method for quantitative and qualitative analysis of functional proteins is western blot (He et al 2022; Wan et al 2022; Yu et al 2020b). There are many reference genes for qRT-PCR in studies of H. armigera , e.g., GAPDH was evaluated as the most stable reference gene in larvae subjected to mechanical injury or nuclear polyhedrosis virus infection (Shakeel et al 2015); tubulin was recognized as the stable gene across different developmental stages (Chandra et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most commonly used research method for gene detection is qRT-PCR, which detects the expression level of the target gene quickly and with great sensitivity (Dong et al 2022; Liu et al 2022a; Yang et al 2021). The most commonly used method for quantitative and qualitative analysis of functional proteins is western blot (He et al 2022; Wan et al 2022; Yu et al 2020b). There are many reference genes for qRT-PCR in studies of H. armigera , e.g., GAPDH was evaluated as the most stable reference gene in larvae subjected to mechanical injury or nuclear polyhedrosis virus infection (Shakeel et al 2015); tubulin was recognized as the stable gene across different developmental stages (Chandra et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, ascoviruses use host cellular apoptotic processes to form their vesicles (Bideshi et al ., 2005, Federici et al ., 2009). Our previous study demonstrated that the replication of HvAV‐3h requires high CaN activity (Yu et al ., 2020a). Abnormality of CaN will lead to dysfunction of its participation in downstream pathways, including apoptosis (Quadroni et al ., 1998; Olofsson et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Infection with HvAV‐3h can significantly inhibit the growth and development of S. exigua , Spodoptera litura and H. armigera larvae (Li et al ., 2013; Hu et al ., 2016; He et al ., 2020). In addition, a recent study has shown that calcineurin (CaN), an enzyme involved in some immune responses of insects, increases its activity after HvAV‐3h infection, which is beneficial for HvAV‐3h replication (Yu et al ., 2020a). These results indicated that how HvAV‐3h overcomes or coexists with the humoral immunity of host larvae is closely related to its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Ascovirus infections show tissue specificity, and according to histopathological observations the guts of S. frugiperda , S. ornithogalli , S. exigua , S. eridania , H. virescens , H. zea , Autographa precationis , and Feltia subterranea are not infected by ascovirus (Hamm et al ., 1998). However, during our previous study on host larval response to HvAV‐3h infection, we observed expression of the major capsid protein (MCP) encoded by HvAV‐3h in the midgut of 3rd‐instar S. exigua larvae (Yu et al ., 2020). MCP and several other virally encoded structural proteins and enzymes are used to identify the viral evolution among different viral species (Cheng et al ., 2003; Zhao & Cui, 2003; Salem et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%